Efektifitas Air Rebusan Daun Kelor Terhadap Hipertensi Gestasional Ibu Hamil di Puskesmas Alai Tahun 2025 - Hasanalita Hasanalita; Epi Satria; Yen Risa Sanputri; Putri Permata Sari; Afrah Diba Faisal (Jurnal Ners, 2025)
One classification of hypertension in pregnancy is gestational hypertension. Gestational hypertension is hypertension that occurs when blood pressure is > 140/90 mmHg at a gestational age of > 20 weeks without a history of previous hypertension and without proteinuria. Pharmacological treatments commonly used in the treatment of hypertension in pregnancy are labetalol, methyldopa, nifedipine, clonidine, diuretics, and hydralazine. Labetalol is the safest drug. Diuretics and CCBs (nifedipine) may be safe but data is minimal and are not used as firstline drugs. According to ACC / AHA 2017 and ESC / ESH 2018, the recommended antihypertensive drugs in pregnancy are only labetalol, methyldopa and nifedipine, while those prohibited are ACE inhibitors, ARBs and direct renin inhibitors (Aliskiren). The purpose of this study was to determine the effect of giving boiled Moringa oleifera leaves on gestational hypertension in pregnant women at the Alai Health Center. The results of statistical tests showed that the average blood pressure of hypertensive pregnant women before being given boiled water from moringa leaves was a systolic mean of 39.391 and a diastolic mean of 30.758. The average blood pressure of hypertensive patients after being given boiled water from moringa leaves was a systolic mean of 15.422 and a diastolic mean of 21.903. There was an effect on systolic blood pressure and a difference in diastolic with a p value of 0.000. There was a significant effect of giving boiled water from moringa leaves (Moringa oleifera) on reducing blood pressure in hypertensive patients at the Alai Health Center. It is hoped that the Head of the Alai Health Center through health workers can provide counseling or socialize to the community that boiled moringa leaves have an effect on reducing blood pressure.